THE DEVELOPMENT OF A CHEMOENTREPRENURSHIP (CEP) ORIENTED COLLOID CHEMISTRY E-MODULE ASSISTED BY 3D PAGE FLIP PROFESSIONAL - Herdini Herdini; Maria Erna; Nursya Alma Indah (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2022)
The development of a chemoentrepreneurship (CEP) oriented Colloidal Chemistry E-Module assisted by 3D Page Flip Professional (3D PFP) is important to with produce students teaching material products that are related to their daily life environment and can stimulate students to create economically valuable and independent products. . To produce a very valid E-Module product, the user response is very good and it looks very attractive, research and development (R&D) is carried out with a 4-D model (Define, Design, Develop and Disseminate). The results of the validity of material and media experts on the developed E-Module are 95.54% and 95.5%, respectively, with a very valid category. The results of the limited test, namely a one-on-one test on 3 students, obtained information that the E-Module needed to be revised. While the user test results from 3 chemistry teachers obtained an average questionnaire score of 94% with very good criteria. Then the results of a limited test of 30 students obtained an average score of 88% with very interesting criteria. The resulting CEP-oriented E-Module products assisted by 3D PFP are expected to increase students' entrepreneurial interest.PENGEMBANGAN E-MODUL KIMIA KOLOID BERORIENTASI CHEMOENTREPRENURSHIP (CEP) BERBANTUAN 3D PAGE FLIP PROFESSIONAL AbstrakPengembangan E-Modul Kimia Koloid berorientasi chemoentrepreneurship (CEP) berbantuan 3D Page Flip Professional (3D PFP) penting dilakukan untuk menghasilkan peserta didik produk bahan ajar yang berhubungan dengan lingkungan kehidupan sehari-hari dan dapat menstimulus peserta didik untuk membuat produk bernilai secara ekonomis dan mandiri. Untuk menghasilkan produk E-Modul yang sangat valid, respon pengguna sangat baik dan tampilannya sangat menarik dilakukan penelitian dan pengembangan (R&D) dengan model 4-D (Define, Design, Develop dan Disseminate). Hasil validitas ahli materi dan media terhadap E-Modul yang dikembangkan berturut-turut adalah 95,54% dan 95,5% dengan kategori sangat valid. Hasil uji terbatas yaitu uji satu-satu terhadap 3 orang peserta didik diperoleh informasi bahwa E-Modul perlu direvisi. Sedangkan hasil uji pengguna dari 3 orang guru kimia diperoleh skor rata-rata angket sebesar 94% dengan kriteria sangat baik. Kemudian hasil uji terbatas terhadap 30 orang peserta didik diperoleh skor rata-rata angket sebesar 88% dengan kriteria sangat menarik. Produk E-Modul berorentasi CEP berbantuan 3D PFP yang dihasilkan diharapkan dapat meningkatkan minat kewirausahaan peserta didik.How To Cite: Herdini, Erna, M., Indah, N.A. (2022). Pengembangan E-Modul Kimia Koloid Berorientasi Chemoentreprenurship (CEP) Berbantuan 3D Page Flip Professional. EDUSAINS, 14 (1) : 50-62.